2013
DOI: 10.4314/just.v32i3.3
|View full text |Cite
|
Sign up to set email alerts
|

Ear, Nose and Throat Manifestations in Geriatrics

Abstract: The aim of this study is to present my observation of the common ear, nose and throat conditions in geriatrics, i.e. in the old age patients. This is a retrospective study analysis of 417 geriatric patients that presented at the Ear, Nose and Throat (ENT) clinic at the Komfo Anokye Teaching Hospital between January 2006 and December 2010. The diagnosis in each patient was based on the history, clinical findings and investigations done on each patient at the time of presentation. The patients were aged between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Sociodemographic features of geriatric emergency in this study revealed a high prevalence of age group 60 -64 years, female preponderance and predomi- [17]. This could be due to the geographical difference in the study population.…”
Section: Discussionmentioning
confidence: 50%
“…Sociodemographic features of geriatric emergency in this study revealed a high prevalence of age group 60 -64 years, female preponderance and predomi- [17]. This could be due to the geographical difference in the study population.…”
Section: Discussionmentioning
confidence: 50%